Remediering som kunstpædagogisk strategi: Mellem film og teater - Christoffersen, Erik Exe (Peripeti, 2011)
Christoffersen analyses a theatrical production process he conducted with university students. The art pedagogical project was based upon the pedagogical and artistic strategy of ‘remediation’, inspired by contemporary art projects by Tue Biering and Jeppe Christensen among others. Christofferesen describes and analyses a particular form of group and identity formation through theatrical re-mediation and combination of filmic narratives with the biographies of the participants.